Dirty Larry - Hamsa, Bobbie; Sharp, Paul (Danbury, Conn. : Children's Press, 1983)
Dirty Larry is never clean except when he is in the shower.
1.4
1.5.
K-3
P-2.
Keywords: Cleanliness -- Fiction; Cleanliness -- Fiction; Readers (Elementary).